PEMBELAJARAN BAHASA INGGRIS BERBASIS BLENDED LEARNING DI ERA NEW NORMAL DENGAN MENGGUNAKAN “MISSING PIECES ACTIVITIES” - Samiko Samiko (Universitas Maritim AMNI Semarang, 2023)
Since Covid-19 attacked several parts of the world, students are suggested to do distance learning. However, since New Normal era, students are allowed to do offline learning by implementing health protocol. This research is aimed to describe teaching method with blended learning model namely “Missing Pieces Activities” in English Subject for Seventh Class Junior High School 2 Bendungan Trenggalek-East Java. This teaching method involves various activities, they are: Missing Words for listening, Missing Small Thing speaking, and Missing Sentences for Reading. With this blended learning model, the activities are done by combining the online learning and offline learning. Source of data in this research is activities done by the students during the teaching and learning process. The data was collected through observation and interview. The finding of the research shows that students are more actively involved in the teaching and learning process. Further, they have higher motivation in learning due to the various activities they did in learning process. Therefore, this Missing Pieces Activities can be one of learning methods in New Normal Era to increase students’ activeness and motivation both in distance and offline learning.